2020
DOI: 10.1016/j.celrep.2020.01.066
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Metabolite 4-Cresol Improves Glucose Homeostasis and Enhances β-Cell Function

Abstract: Highlights d Serum concentrations of 4-cresol are inversely correlated with type 2 diabetes d Non-toxic dose of 4-cresol reduces adiposity, glucose intolerance, and liver fat d 4-Cresol stimulates insulin secretion and b-cell proliferation in vivo and in vitro d 4-Cresol downregulates pancreatic and islet expression of the kinase DYRK1A

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 52 publications
1
36
2
1
Order By: Relevance
“…Although a receptor has not yet been identified, ImP was shown to directly inhibit hepatic insulin receptor substrate signalling in mice, with p38 mitogen-activated protein kinase (MAPK)-mediated hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) being identified as a central regulatory mechanism [ 98 ]. In a recent study in humans on the extreme end of cardiometabolic disease (obese and hyperglycaemic), the microbial metabolite 4-cresol negatively correlated with type 2 diabetes [ 99 ]. Although 4-cresol can be derived directly from food, it is also a product of tyrosine and phenylalanine fermentation in the colon.…”
Section: Gut Microbe-derived Metabolites Alter Endogenous Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a receptor has not yet been identified, ImP was shown to directly inhibit hepatic insulin receptor substrate signalling in mice, with p38 mitogen-activated protein kinase (MAPK)-mediated hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) being identified as a central regulatory mechanism [ 98 ]. In a recent study in humans on the extreme end of cardiometabolic disease (obese and hyperglycaemic), the microbial metabolite 4-cresol negatively correlated with type 2 diabetes [ 99 ]. Although 4-cresol can be derived directly from food, it is also a product of tyrosine and phenylalanine fermentation in the colon.…”
Section: Gut Microbe-derived Metabolites Alter Endogenous Metabolismmentioning
confidence: 99%
“…Although 4-cresol can be derived directly from food, it is also a product of tyrosine and phenylalanine fermentation in the colon. Subcutaneous administration of 4-cresol prevented development of hyperglycaemia and fatty liver in mice fed a high-fat diet [ 99 ]. In line with observations that 4-cresol increases insulin secretion, this metabolite downregulated the expression of dual-specificity tyrosine-regulated kinase-1a (DYRK1A) [ 99 ], which has been shown to facilitate pancreatic beta cell proliferation [ 100 ].…”
Section: Gut Microbe-derived Metabolites Alter Endogenous Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, both animal [ 3 , 4 ] and human [ 5 , 6 , 7 ] studies have recognized microbiota-derived metabolites—such as short chain fatty acids (SCFA), 4-cresol, and imidazole propionate—as potential drivers of insulin resistance in MetSyn and DM2 [ 2 , 8 , 9 , 10 , 11 ]. However, many questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that metabolites produced by intestinal bacteria regulate β-cell functions in diabetes (39). In addition, foods fermented with koji mold activate intestinal bacteria (40).…”
Section: Discussionmentioning
confidence: 99%